GANGSTER SI CANTIK Program: The Implementation of Character Building for Elementary School Students - Rachmadyanti, Putri; Bintang Nusantara, Andre; Setiawan, Ricky; Suprayitno, Suprayitno; Kiettikunwong, Narong (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
This study aims to identify and produce valid information about character education development programs in elementary schools, along with character identification developed from the Gangster Si Cantik program. This is a follow-up on overcoming character education problems that occurred in schools after the pandemic. This is important for conducting this research comprehensively to develop the character of elementary school students. This research used qualitative research with the type of case study to school programs at Dr. Sutomo 5 Surabaya Elementary School, East Java, Indonesia. The study was conducted by collecting data and information through purposive sampling, from 7 respondents consisting of the principal, teachers, and 5 students. The results of the research include the background of the formation of Gangster Si Cantik and character development strategies by Gangster Si Cantik. Based on student and teacher interviews there are good changes in the attitude of friends for the better despite it requiring some time and process. The characters developed through Gangster Si Cantik include caring, cooperation, fairness, honesty, discipline, and peace-loving. The constraints of this program are the limited time when traveling around and the limited number of aspiration boxes. This program is a form of collaboration between principals, teachers, and students in solving character education problems in elementary schools to create a safe and peaceful school environment. Collaboration is essential for future research in every aspect. It is intended that the findings of this study will enhance the practice of character development in elementary schools through scientific references.